Students' and Instructors' Understandings, Attitudes and Beliefs about Educational Theories: Results of a Mixed-Methods Study - Stefan T. Siegel; Martin Daumiller (MDPI AG, 2021)
(1) Background: Educational theories are a constitutive element of educational studies. Despite their theoretical relevance, little is still known about students' and instructors' understandings of educational theories and their theory-related attitudes and beliefs. (2) Methods: To elucidate these constructs and to test their relevance, we conducted a mixed-methods study with 32 students and 12 instructors of educational studies at a German university. (3) Results: We found that both groups perceived educational theories as rather abstract concepts. Students reported rather negative attitudes and naive beliefs. For both groups, we found that attitudes and beliefs were strongly tied to motivational and affective aspects when dealing with educational theories, which stresses their relevance for educational studies. (4) Conclusions: We suggest a systematic theoretical clarification of the term educational theories. Furthermore, consideration of students' and instructors' theory-related attitudes and beliefs can give rise to meaningful practical implications (e.g., through self-reflection).